The Staphylococcus epidermidis Transcriptional Profile During Carriage - Teichmann, Pascâl; Both, Anna; Wolz, Christiane; Hornef, Mathias W.; Rohde, Holger; Yazdi, Amir S.; Burian, Marc (Frontiers in Microbiology, 2022)
The virulence factors of the opportunistic human pathogen Staphylococcus epidermidis have been a main subject of research. In contrast, limited information is available on the mechanisms that allow the bacterium to accommodate to the conditions during carriage, a prerequisite for pathogenicity. Here, we tested the hypothesis that the adaptation of S. epidermidis at different anatomical sites is reflected by differential gene regulation. We used qPCR to profile S. epidermidis gene expression in vivo in nose and skin swabs of 11 healthy individuals. Despite some heterogeneity between individuals, significant site-specific differences were detected. For example, expression of the S. epidermidis regulator sarA was found similarly in the nose and on the skin of all individuals. Also, genes encoding colonization and immune evasion factors (sdrG, capC and dltA), as well as the sphingomyelinase encoding gene sph, were expressed at both anatomical sites. In contrast, expression of the global regulator agr was almost inactive in the nose, but readily present on the skin. A similar site-specific expression profile was also identified for the putative chitinase-encoding SE0760. In contrast, expression of the autolysine-encoding gene sceD, and the wall teichoic acid (WTA) biosynthesis gene tagB were more pronounced in the nose as compared to the skin. In summary, our analysis identifies site-specific gene expression patterns of S. epidermidis during colonization. In addition, the observed expression signature was significantly different from growth in vitro. Interestingly, the strong transcription of sphingomyelinase together with the low expression of genes encoding the tricarboxylic acid cycle suggests very good nutrient supply in both anatomical niches, even on the skin where one might have suspected a rather lower nutrient supply compared to the nose.